Molecular Modelling of the H2‐Adsorptive Properties of Tetrazolate‐Based Metal−Organic Frameworks: From the Cluster Approach to Periodic Simulations. Issue 11 (26th April 2018) - Brea, Oriana; Luna, Alberto; Díaz, Cristina; Corral, Inés
Abstract: Hydrogen has been proposed as a long‐term non‐fossil fuel to be used in a future ideal carbon‐neutral energetic economy. However, its low volumetric energy density hinders its storage and transportation. Metal−organic frameworks (MOFs) represent very promising materials for this purpose due to their very extended surface areas. Azolates, in particular tetrazolates, are – together with carboxylate functionalities – very common organic linkers connecting metallic secondary building units in MOFs. This study addresses, from a theoretical perspective, the H2 adsorptive properties of tetrazolate linkers at the molecular level, following a size‐progressive approach. Specifically, we have investigated how the physisorption energies and geometries are affected when changing the environment of the linker by considering the azolates in the gas phase, immersed in a finite cluster, or being part of an infinite extended crystal material. Furthermore, we also study the H2 adsorptive capacity of these linkers within the cluster model. Abstract : Gas‐phase and periodic boundary condition simulations on the H2 ‐adsorptive properties of [Mn II 3 O(HNDT)2 (NDT)(DMF)3 ] metal−organic frameworks reveal that secondary building units and linkers are able to adsorb at least 30 H2 molecules. H2 molecules are found to physisorb coplanar to the tetrazolate groups, and in the vacancies defined by trios and pairs of adjacent tetrazolates, with average physisorption energies that amount to 9.5 kJ mol −1 .